A highly efficient, in situ wet-adhesive dextran derivative sponge for rapid hemostasis. (June 2019) - Liu, Chunyu; Liu, Xia; Liu, Chenyu; Wang, Ning; Chen, Hailiang; Yao, Weihe; Sun, Guozhen; Song, Qiling; Qiao, Weihong
Abstract: Uncontrolled hemorrhage is closely related to the high risk of death. However, local hemostats still have various defects and side effects. Herein, an aldehyde dextran (PDA) sponge with proper absorption and adhesion properties is developed for hemorrhage control. PDA sponge with pore size of ∼30–50 μm fabricated by lyophilization not only absorbs blood quickly (47.7 g/g), but also possesses strong tissue adhesion (∼100 kPa). PDA sponge with low cytotoxicity and hemolysis achieves effective hemostasis and remarkable blood loss reduction in the ear vein, femoral artery and liver injuries of rabbit models. Furthermore, the exploration of hemostatic mechanisms related to tissue, blood, plasma, cells and coagulation system indicates that PDA sponge can significantly accelerate coagulation by rapid wound block, fast cells aggregation and initiation, and high coagulation factors concentration, instead of by the coagulation cascade activation. Importantly, this hemostat exhibits excellent biodegradability and nearly no skin irritation. Overall, the biodegradable and tissue adhesive PDA sponge will be a promising quick-hemostatic dressing for uncontrollable hemorrhage. Graphical abstract: Image 1